Assessment of nutritional composition and bioactive compounds of various wild potato cultivars in Bangladesh - Md. Abu Zubair; Md. Esrafil; Faruk Hosen; Adrita Afrin (International Journal of Food Properties)
This study was designed to determine the nutritional composition and bioactive compounds in four selected wild potato varieties. Moisture content in wild potato varieties ranged between 70.92 ± 0.29 to 73.82 ± 0.64 g/100 g sample. Shimul Alu has the highest amount of ash (1.01 g/100 g sample). The range of 3.2–4.10 g/100 g sample was the range where the protein content changed substantially. Jam Alu had the highest protein content (4.10 g/100 g sample), whereas lal parki had the lowest value (2.2 g/100 g sample). Shimul Alu provided the highest crude fiber concentration (0.55 g/100 g sample), whereas lal parki presented the lowest crude fiber content (0.43 g/100 g sample). Shimul Alu had the highest levels of starch and reducing sugar. In comparison to widely grown types, wild potato varieties showed increased antioxidant activity. Jam Alu had the most antioxidant activity, with 148.83 mol of ascorbic acid per gram, whereas commonly consumed potato, lal parki, had the lowest antioxidant activity, with 91.57 mol of ascorbic acid per gram. The phenolic content of the dry sample ranged from 1.01 to 2.85 mg GAE. Jam alu, one of the potato cultivars, had the greatest phenolic content. The range of the total flavonoid concentration in grams was 18.04–41.38 mg of quercetin equivalents (QE). Shil bilati, a wild kind of potato, had the highest flavonoid content, whereas lal parki, a commonly consumed potato, had the lowest. In comparison to widely farmed and consumed forms, wild kinds of potatoes were shown to be more nutrient-dense.